Contribuição ao conhecimento químico de plantas do nordeste Vatairea macrocarpa (Benth.) Ducke - Silva, Maria Goretti de Vasconcelos (1987)
Vatairea macrocarpa Ducke is a medium size tree wich a very bitter wood which is largely used in woodworks [...]